Communication Management Mafindo Samarinda as An Anti-Hoax Facilitator - Amalia, Nabilah; Arum Sary, Kezia (Jurnal Indonesia Sosial Teknologi, 2024)
In the digital information age, the spread of misinformation or hoaxes is a serious challenge for society. The Anti-Defamation, Hoax, and Intolerance Community Organization (Mafindo) in Samarinda has become a facilitator in efforts to prevent and overcome the spread of hoaxes. This study aims to analyze communication management applied by Mafindo Samarinda as an anti-hoax facilitator. The research method used is a case study with a qualitative approach. Data was obtained through interviews with Mafindo Samarinda members, observations of activities carried out, and analysis of documents related to anti-hoax campaigns that have been run by this organization. The results showed that Mafindo Samarinda implemented a well-planned communication management strategy. They use various communication channels, such as social media, seminars, and workshops, to disseminate correct information and educate the public on how to identify hoaxes. In addition, Mafindo Samarinda also collaborates with various parties, including the government and educational institutions, in a joint effort to fight the spread of hoaxes. Nevertheless, the challenges faced by Mafindo Samarinda are not small. An active role from all levels of society is needed to ensure the success of this anti-hoax program. Therefore, effective communication management needs to be continuously developed and adapted to technological developments and community dynamics.